The Greatest Comets in History - Seargent, David A.J. (Springer, 2017)
Comets have fascinated and awed humankind since ancient times. Of the thousands of comets recorded throughout history, those deemed to have been the most spectacular have been described in the accounts of eyewitnesses and often recorded in official documents. This book introduces you to the greatest of the greats, starting with the comet in 372 B. C. called "Aristotle’s Comet" and ending with the spectacular appearance of McNaught’s Comet in 2007. There is an introductory chapter explaining what comets are and how they are classified, and correcting a few popular misconceptions. Later in the book you will read about the different returns of Halley’s Comet and the Kreutz sungrazing group, often called the kamikaze comets. There is even a chapter on comets that were visible in broad daylight.